Design and experiment of nonlinear absorber for equal-peak and de-nonlinearity. (9th June 2019) - Sun, Xiuting; Xu, Jian; Wang, Feng; Cheng, Li
Abstract: This paper generalizes and modifies the Equal-peak method for the design of nonlinear vibration absorber for use in the vibration suppression of nonlinear primary vibration system. For a vibration system with nonlinearity, the most relevant bandwidth is the resonance band, in which the undesirable nonlinear vibration phenomenon occurs because of the dramatically amplified of vibration amplitude. To generalize the Equal-peak method for a complex nonlinear primary system under force/base excitations, we utilize the nonlinear perturbation method and bifurcation theory to investigate the vibration performances and critical conditions for dynamical transition. In addition to the Equal-peak property, another novel advantage, called De-nonlinearity (introduced by coupling nonlinearity), is revealed for vibration control in addition to the known effect of nonlinearity on vibration suppression. It is discovered that by applying the nonlinear vibration absorber with appropriate design on the NL primary system, the Equal-peak property can be accurately realized, and unexpected nonlinear vibration performances can be effectively eliminated. A relevant experimental prototype is carried out to illustrate the Equal-peak and De-nonlinearity properties, which is composed of a primary vibration system with complex nonlinearity and a designed tunable nonlinear vibration absorber. The proposed modified design method for Equal-peak and De-nonlinearity properties has huge potential application in the vibration suppression for low-frequency and strong nonlinearity fields such as ships, aircrafts and ocean platform. Highlights: Explore a modified nonlinear tuning method for the design of nonlinear vibration absorber. Realize accurate equal-peak property for different parameters changing in large ranges. Obtain expressions of nonlinear frequencies and peaks for multi-nonlinearity system. Design appropriate nonlinearity to eliminate undesired nonlinear vibration performances. Introduce the Origami structure to assemble a tunable nonlinear vibration absorber.